2014
DOI: 10.1016/j.nbd.2013.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Microglial derived tumor necrosis factor-α drives Alzheimer's disease-related neuronal cell cycle events

Abstract: Massive neuronal loss is a key pathological hallmark of Alzheimer’s disease (AD). However, the mechanisms are still unclear. Here we demonstrate that neuroinflammation, cell autonomous to microglia, is capable of inducing neuronal cell cycle events (CCEs), which are toxic for terminally differentiated neurons. First, oligomeric amyloid-beta peptide (ApO)-mediated microglial activation induced neuronal CCEs via the tumor-necrosis factor-α (TNFα) and the c-Jun Kinase (JNK) signaling pathway. Second, adoptive tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 125 publications
(79 citation statements)
references
References 88 publications
(108 reference statements)
3
76
0
Order By: Relevance
“…Overall, cytokine expression was higher in R1.40 mice than Non-Tg mice and cytokine expression increased at 120 DPI compared to 3 DPI. This finding is consistent with previous studies showing that cytokine expression is enhanced in R1.40 mice at six months of age 65 This article has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction. The final published version may differ from this proof.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, cytokine expression was higher in R1.40 mice than Non-Tg mice and cytokine expression increased at 120 DPI compared to 3 DPI. This finding is consistent with previous studies showing that cytokine expression is enhanced in R1.40 mice at six months of age 65 This article has been peer-reviewed and accepted for publication, but has yet to undergo copyediting and proof correction. The final published version may differ from this proof.…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, the activation of MAPK signalling occurs via cellular stress arising from inflammatory cytokines such as TNFα [46] or Aβ plaques [47]. We showed that elevated phosphorylation of Erk1/2 in the neocortex and brainstem is associated with Aβ plaques and increased TNFα expression, respectively, as well as increased apoptosis-inducing caspase3 levels in the brainstem.…”
Section: Discussionmentioning
confidence: 99%
“…103 Clustering of activated microglia and astrocytes have been reported surrounding A plaques and correlated with elevated inflammatory cytokines such as interleukin (IL)-1, IL-6, and tumor necrosis factor-. 104,105 Furthermore, peripheral monocytes/macrophages are capable of clearing vascular A . 106 In an in vivo multi-photon imaging study, circulating monocytes have been shown to enter luminal walls of A -positive veins and carry amyloid back into the bloodstream.…”
Section: Neuroinflammationmentioning
confidence: 99%